Advancing Seaport Resilience to Natural Hazards Due to Climate Change: Strategies to Overcome Decision Making Barriers - Mclean, Elizabeth L.; Becker, Austin (Frontiers in Sustainability, 2021)
Climate change and extreme weather events put in peril the critical coastal infrastructure that is vital to economies, livelihoods, and sustainability. However, for a variety of reasons, decision makers often do not implement potential adaptation strategies to plan and adjust to climate and extreme weather events. To respond to the question of how seaport decision makers perceive strategies to overcome the barriers to adaptation we used semi-structured interviews of 30 seaport directors/managers, environmental specialists, and safety managers from 15 medium- and high-use ports of the U.S. North Atlantic. This paper contributes four broad strategies identified by seaport decision makers as necessary to help them advance on this challenge: funding, better planning or guidance, research and education, and advocacy/lobbying. We coded these strategies parallel to our partner paper that identified seven key barriers faced by the same set of decision makers. Results can help direct resources in ways targeted to the needs of seaport decision makers. The proposed framework contributes to theories of resilience building and barriers to decision making. Being strategic about change facilitates effective adaptation, decreasing risk, and enables continuity of safe, and sustainable, operations of U.S. seaports in the face of climate and extreme weather events.